BIROKRASI KONTEMPORER INDONESIA ANTARA REFORMASI DAN REALITAS: EVALUASI SISTEM MERIT DALAM PENGUATAN TATA KELOLA PEMERINTAHAN YANG BAIK - Richard Djiko (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2026)
Bureaucratic reform has become one of the strategic agendas of governance in Indonesia since the Reform Era, aiming to create a professional, accountable, and high-performing public administration system. One of the key instruments introduced to achieve this objective is the merit system, which emphasizes competence, qualifications, performance, and fairness in the management of civil servants. However, despite significant regulatory progress, the implementation of the merit system continues to face various challenges at both the central and local government levels. This study aims to evaluate the implementation of the merit system in contemporary Indonesian bureaucracy and to analyze its contribution to strengthening good governance. The research employs a qualitative approach through a literature review and policy analysis of laws, government regulations, official reports, and relevant scholarly publications. The findings indicate that the merit system has contributed positively to improving transparency in recruitment, career development, and performance management within the civil service. Nevertheless, its implementation remains constrained by political intervention, patronage practices, bureaucratic culture, and disparities in institutional capacity across regions. These conditions create a gap between the ideals of bureaucratic reform and the realities of administrative practice. The study concludes that strengthening the merit system is essential for enhancing accountability, transparency, effectiveness, and public trust in government institutions. Therefore, sustainable bureaucratic reform requires not only regulatory compliance but also the development of a professional and integrity-based bureaucratic culture to support the realization of good governance in Indonesia.